Going Beyond: Lucid Dreaming as a Lens into Transformative Experience Design for Virtual Reality - Kitson, Alexandra; Riecke, Bernhard E. (23rd Annual CyberPsychology, CyberTherapy & Social Networking Conference, 2018)
Technology is rapidly growing and becoming more present in our daily lives. Yet, rather than being a source of making our lives easier and more fulfilling, technology is being used as a source of escapism and compulsive consumption of information, and this can lead to a loss of meaningful and authentic connection [1]. Authentic connection is important in sustaining positive well-being and relationships. Technologies, such as social platforms aimed at connecting people exist, but are often used superficially and do not provide that meaningful connection people seek. Emerging technologies such as virtual reality (VR) are fundamentally different, unlike smartphones or screens, in the way they can immerse users and have the potential to alter their behaviour and mental state [3,4]. So, it becomes essential that designers carefully study the implications of VR for its users, and consider the human perspective when creating these experiences in order to keep the human condition intact. Especially in the fields of VR, we are in uncharted territory – a vast amount of applications and content yet with little or no regulation. Without standards and guidelines for effective VR content, we diminish the potential for harnessing this technology for positive experiences and well-being. Researchers in the past decade have investigated how VR might be used to facilitate transformative experiences, sudden and profound changes in the self-world [2], by creating novel opportunities for learning and insight [5,6,7,8]. More recently, the human-computer interaction community has emphasized the use of interaction design for promoting positive health and well-being [9]. From this research, the fields of Positive Technology [10,11] and Positive Computing [12] have formed with the goal of applying a scientific-based approach to designing interactive systems for well-being and positive change [1,6]. A key challenge interaction designers face is designing for technologies that are purposefully built to foster transformative experiences. One possible way to approach this challenge is to ground VR experience design in real human experiences; there happens to exist a transformative experience that very closely mimics VR – lucid dreaming. Lucid dreaming is the experience of knowing one is dreaming while dreaming, giving the lucid dreamer the opportunity to control or shape their dream. In terms of transformative experiences, lucid dreaming is similar to VR in that they both have the potential to manipulate bodily self-consciousness, embody another person's subjective experience, and alter laws of logic and nature. Moreover, both lucid dreaming and VR can alter bodily self-consciousness, allow people to embody another, and simulate impossible worlds. Therefore, we can use lucid dreaming experiences as a lens into how to design for VR transformative experiences. One study so far has looked at applying lucid dreaming to VR transformative experience design [13] and one of the new insights gleaned was to incorporate ceremony into the experience. That is, use rituals or preparations designed to ease the user into and out of the transformative VR experience in order to give users time to open themselves mentally for a profound experience and reflect on their shift in worldview after. From this one study, we can see there is much to learn from these somewhat mystical or spiritual experiences of altered consciousness. Yet, much work has to be done in validating the theoretical design implications. References [1] Gaggioli, A., Riva, G., Peters, D., & Calvo, R. A. (2017). Positive Technology, Computing, and Design: Shaping a Future in Which Technology Promotes Psychological Well-Being. Emotions and Affect in Human Factors and Human-Computer Interaction (pp. 477–502). Elsevier. doi:10.1016/B978-0-12-801851-4.00018-5 [2] Gaggioli, A. (2016). Transformative experience design. Human Computer Confluence. Transforming Human Experience Through Symbiotic Technologies, 96–121. [3] Cobb, S. V. G., Nichols, S., Ramsey, A., & Wilson, J. R. (1999). Virtual Reality-Induced Symptoms and Effects (VRISE). Presence: Teleoperators and Virtual Environments, 8(2), 169–186. doi:10.1162/105474699566152 [4] Morina, N., Ijntema, H., Meyerbröker, K., & Emmelkamp, P. M. G. (2015). Can virtual reality exposure therapy gains be generalized to real-life? A meta-analysis of studies applying behavioral assessments. Behaviour Research and Therapy, 74(Supplement C), 18–24. doi:10.1016/j.brat.2015.08.010 [5] Gaggioli, A., Chirico, A., Triberti, S., & Riva, G. (2016). Transformative Interactions: Designing Positive Technologies to Foster Self-Transcendence and Meaning. ANNUAL REVIEW OF CYBERTHERAPY AND TELEMEDICINE 2016, 169. [6] Botella, C., Banos, R. M., & Guillen, V. (2017). Positive Technologies for Improving Health and Well-Being. In C. Proctor (Ed.), Positive Psychology Interventions in Practice (pp. 219–234). Springer International Publishing. doi:10.1007/978-3-319-51787-2_13 [7] Roo, J. S., Gervais, R., Frey, J., & Hachet, M. (2017). Inner Garden: Connecting Inner States to a Mixed Reality Sandbox for Mindfulness. Proceedings of the 2017 CHI Conference on Human Factors in Computing Systems, CHI ’17 (pp. 1459–1470). New York, NY, USA: ACM. doi:10.1145/3025453.3025743 [8] Villani, D. (Ed.). (2016). Integrating technology in positive psychology practice. Advances in psychology, mental health, and behavioral studies (APMHBS) book series. Hershey, PA: Information Science Reference, an imprint of IGI Global. [9] Calvo, R. A., & Peters, D. (2015). Introduction to Positive Computing: Technology That Fosters Wellbeing. Proceedings of the 33rd Annual ACM Conference Extended Abstracts on Human Factors in Computing Systems, CHI EA ’15 (pp. 2499–2500). New York, NY, USA: ACM. doi:10.1145/2702613.2706674 [10] Botella, C., Riva, G., Gaggioli, A., Wiederhold, B. K., Alcaniz, M., & Ba?os, R. M. (2012). The Present and Future of Positive Technologies. Cyberpsychology, Behavior, and Social Networking, 15(2), 78–84. doi:10.1089/cyber.2011.0140 [11] Riva, G., Banos, R. M., Botella, C., Wiederhold, B. K., & Gaggioli, A. (2012). Positive Technology: Using Interactive Technologies to Promote Positive Functioning. Cyberpsychology, Behavior, and Social Networking, 15(2), 69–77. doi:10.1089/cyber.2011.0139 [12] Calvo, R. A., & Peters, D. (2014). Positive Computing: Technology for Wellbeing and Human Potential. MIT Press. [13] Kitson, A., Schiphorst, T., & Riecke, B. E. (2018). Are You Dreaming? A Phenomenological Study on Understanding Lucid Dreams as a Tool for Introspection in Virtual Reality. Proceedings of the 2018 CHI Conference on Human Factors in Computing Systems, CHI ’18 (accepted). Montreal, ON, Canada: ACM. doi:10.1145/3173574.3173917
Keywords: Riecke; Riecke_2018; alex-kitson; bernhard-riecke; conferenceTalksWithoutPaper; lucid-dreaming; talkWithoutPaper; transformative-experiences